Manipulation resolves non-trivial structure of corrole monolayer on Ag(111). (2nd December 2015) - Tebi, Stefano; Aldahhak, Hazem; Serrano, Giulia; Schöfberger, Wolfgang; Rauls, Eva; Schmidt, Wolf Gero; Koch, Reinhold; Müllegger, Stefan
Abstract: Non-trivial arrangement of molecules within a molecular network complicates structure determination due to interdigitation, partial overlap, or stacking. We demonstrate that combined imaging and lateral manipulation with a scanning tunneling microscope resolves the intricate structure of a molecular network in two-dimensions in a straightforward manner. The network, formed by a monolayer of 5, 10, 15-tris(pentafluorophenyl)-corrole molecules on Ag(111), is manipulated for the first time with single-molecule precision. Our results reveal a shingle-like packing of partially overlapping corrole molecules. Density functional theory calculations support our findings.